Effects of land‐use changes on plant functional and taxonomic diversity along a productivity gradient in wet meadows. (2nd August 2013) - Janeček, Š.; de, F.; Horník, J.; Bartoš, M.; Černý, T.; Doležal, J.; Dvorský, M.; Fajmon, K.; Janečková, P.; Jiráská, Š.; Mudrák, O.; Klimešová, J.; et al.
Abstract Questions To what extent do changes in management (abandonment and fertilization) affect plant functional and taxonomic diversity in wet meadow communities? To what extent do the changes in functional and taxonomic diversity depend on site productivity? Location Železné hory Mts., Czech Republic. Methods Experimental plots were established on 21 wet meadows differing in productivity and species composition. In each meadow, in 2007, four 1 × 1 m plots were established, representing a full factorial design with abandonment and fertilization as the factors. In each plot, the number of species present was recorded in 100 subplots (0.1 × 0.1 m) in the years 2007, 2009 and 2011. Different indicators of functional diversity (functional richness, functional evenness, and Rao′s quadratic entropy) were calculated using five functional traits (SLA, LDMC, seed mass, plant height and clonality). Both abundance‐weighted and non‐weighted diversity indices were calculated. Randomization tests (conducted with PERMANOVA) were used to assess the effect of site productivity and management on both α‐ and β‐diversity components. Results Meadows along the productivity gradient differed in functional and taxonomic diversity. Both abandonment and fertilization decreased taxonomic diversity. Whereas fertilization decreased functional richness and Rao′s quadratic entropy, abandonment decreased functional evenness. The changes in both taxonomic and functional diversity caused by abandonment and fertilization occurred faster in more productive meadows. Conclusions The increased dominance of tall species with abandonment and fertilization, followed by the loss of species and the decrease in various indicators of functional diversity, suggest that increased competition for light resulted in increased trait convergence among co‐existing species. In addition, many processes occurring after abandonment and fertilization depend on meadow productivity. Results suggest that abundance‐ and non‐abundance‐weighted diversity indices give complementary insights on community structure. These results imply that changes are needed in current meadow management and conservation.